Perancangan User Interface Sistem Informasi Monitoring dan Evaluasi Pembangunan Daerah Berbasis Website pada Bappeda Litbang Kota Palembang - Abdurrony Fathoni (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2023)
Palembang City Research and Development Bappeda has several main tasks and is carried out by several different fields, one of which is the field of Regional Development Planning, Control & Evaluation which focuses on preparing regional development planning and budgeting, controlling through monitoring regional programs and activities, as well as carrying out evaluations. and reporting on regional development programs and activities. To carry out several main tasks in the PPEPD field, there are several work tools in the form of systems with running business processes, one of which is the Monitoring and Evaluation Information System (SI MonEv) which is used quarterly. Based on the analysis carried out at the Palembang City Research and Development Bappeda, especially in the field of PPEPD with a system that is already running to assist in carrying out tasks, there are several problems found in the process and its use, namely the inaccurate layout of the features and assets in the system interface, which causes a feeling of discomfort. in its use, and there are no features to support ease of use. Therefore, several system design efforts are needed that are able to provide solutions to problems, convenience, and refresh the existing system. This development takes the form of evaluating and designing the user interface on the system to provide refreshment to the interface and adding features to support ease of operation such as graphical data visualization to simplify the monitoring process, a search feature to simplify the process of searching for reports, notifications to provide notification of each entry of the latest report in order to avoiding missing information, and providing a deadline feature to minimize delays in the reporting process.